Labour supply effects of increasing the female state pension age in the UK from age 60 to 62 - Jonathan Cribb; Carl Emmerson; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2014)
In a previous study we examined the impact on employment of increasing the state pension age for women from age 60 to 61 (Cribb, Emmerson and Tetlow, 2013). This short paper incorporates more recent data, now available up to March 2014, which allows us to study the impact on employment over the period when the female state pension age rose to age 62. Using the same difference-in-differences methodology as before, we find that women's employment rates at ages 60 to 61 were increased by 5.9 percentage points as a result of the state pension age increasing from age 60 to age 62 between April 2010 and March 2014. We find no statistically significant evidence of a different impact on employment between April 2010 and March 2012 (when the state pension age rose from age 60 to 61) and between April 2012 and March 2014 (when it rose from age 61 to 62). The more recent data boost our sample size, allowing us to estimate the impact of the reform with greater precision. However, we continue to find little statistically significant evidence of differences in response among women with different characteristics. The one exception we find is that the rise in the state pension age increases the employment rate of single women by 10.1 percentage points, which is statistically significantly greater (at the 10% level) than the 4.4 percentage point increase we find for women in couples.
Keywords: H55; J21; J26; 330; early retirement age; labour supply; policy reform; retirement